S100A12 Serum Levels and PMN Counts Are Elevated in Childhood Systemic Vasculitides Especially Involving Proteinase 3 Specific Anti-neutrophil Cytoplasmic Antibodies - Brown, Kelly L.; Lubieniecka, Joanna M.; Armaroli, Giulia; Kessel, Katharina; Gibson, Kristen M.; Graham, Jinko; Liu, Dongmeng; Hancock, Robert E. W.; Ross, Colin J.; Benseler, Susanne M.; Luqmani, Raashid A.; Cabral, David A.; et al. (Frontiers in Pediatrics, 2018)
Objectives. Chronic primary systemic vasculitidies (CPV) are a collection of rare diseases involving inflammation in blood vessels, often in multiple organs. CPV can affect adults and children and may be life- or organ-threatening. Treatments for adult CPV, although effective, have known severe potential toxicities; safety and efficacy of these drugs in pediatric patients is not fully understood. There is an unmet need for biologic measures to assess the level of disease activity and, in turn, inform treatment choices for stopping, starting or modifying therapy. This observational study determines if S100 calcium-binding protein A12 (S100A12) and common inflammatory indicators are sensitive markers of disease activity in children and adolescents with CPV that could be used to inform a minimal effective dose of therapy. Methods. Clinical data and sera were collected from 56 participants with CPV at study visits from diagnosis to remission. Serum concentrations of S100A12, C-reactive protein (CRP) and hemoglobin (Hb) as well as whole blood cell counts and erythrocyte sedimentation rate (ESR) were measured. Disease activity was inferred by physician’s global assessment (PGA) and the pediatric vasculitis activity score (PVAS). Results. Serum concentrations of standard markers of inflammation (ESR, CRP, Hb, absolute blood neutrophil count), and S100A12 track with clinically assessed disease activity. These measures – particularly neutrophil counts and sera concentrations of S100A12 – had the most significant correlation with clinical scores of disease activity in those children with vasculitis that is associated with anti-neutrophil cytoplasmic antibodies (ANCA) against proteinase 3. Conclusions. S100A12 and neutrophil counts should be considered in the assessment of disease activity in children with CPV particularly the most common forms of the disease that involve proteinase 3 ANCA.